Pelatihan Starup Digital dan Digital Marketing bagi Siswa-Siswi Sekolah Menengah Atas (SMA) Negeri 1 Metro - Yan Aditiya; Sri Rahayu; Stefanus Rumangkit (Jurnal Pengabdian Masyarakat Madani, 2021)
The Community Service Team (PKM) will carry out PKM activities at SMA Negeri 1 Metro (SMAN 1 Metro), and focus on class XII students, totaling 388 students. This PKM activity was carried out at SMAN 1 Metro because there was no interest from SMAN 1 Metro students for entrepreneurship and still did not understand how to start a business. Based on interviews conducted with several students, it was found that: 1) Students do not have an interest in entrepreneurship, 2) there are students who have an interest in starting entrepreneurship, but still do not have sufficient knowledge, 3) students' lack of knowledge about digital marketing. Therefore, the service team saw that this was one of the challenges for the service team to help SMAN 1 Metro to share knowledge about starting a business and digital marketing. The method used in this PKM activity is the method of socialization / counseling, discussion, simulation, and application. The results of the PKM activities that have been carried out are the presentation of material on E-Business Concept, Social Media Marketing, Management Branding Social Media, Personal Branding, business assistance and proposals for the FIKSI national competition. This PKM activity has a positive impact on students of SMAN 1 Metro, they become inspired to become young entrepreneurs, and have basic knowledge to run a business. The knowledge possessed by students and students will encourage them to ask for entrepreneurship. The material presented made the students know how simple it is to start a business, build a brand by using social media, and build personality as a businessman.